Realidades múltiplas em Grande Sertão Veredas: uma análise fenomenológica - Mascarenha, Denise dos Anjos (2016)
This study aims to examine the multiple realities in the literary work “Grande Sertão: Veredas” by João Guimarães Rosa, from the perspective of Alfred Schuzt’s phenomenology. Walking the path of debate of the function and the participation of literature in the social world, accessing the author's biography to understand the context of his writing and also the author’s intentions. In an exercise of producing a new perspective before a work already so studied, I we apprehend some of the provinces of finite meanings present in the narrative, articulating the experiences of Riobaldo Tatarana and his possible worlds to categories and sociological concepts. In addition to a theoretical discussion about the function of literature, I proposed, based on documentary analysis, to outline a profile of the author's understanding of his role as a writer, and then did the interpretive exercise of some themes present in his narrative Understood as finite provinces of meaning.